2022
DOI: 10.3390/plants11131664
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Main Health-Promoting Compounds and Antioxidant Activity of Different Edible Parts of Purple Flowering Stalks (Brassica campestris var. purpuraria) and Green Flowering Stalks (Brassica campestris var. campestris)

Abstract: Purple flowering stalks and green flowering stalks of Brassica campestris are widely cultivated in the middle and upper reaches of the Yangtze River. Here, concentrations of the main health-promoting compounds and antioxidant capacity levels were characterized in different parts (leaves, peel, flesh, and inflorescences) of purple and green flowering stalks. There were significant differences in the concentrations of health-promoting compounds between the two variants; the concentrations of pigments, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Substantial variations in nutrient contents among different vegetable organs have been documented [ 24 , 31 , 32 ]. In comparison to the other organs studied in this study, the inflorescences contained the highest total ascorbic acid and total phenolic contents, which was consistent with previous studies [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial variations in nutrient contents among different vegetable organs have been documented [ 24 , 31 , 32 ]. In comparison to the other organs studied in this study, the inflorescences contained the highest total ascorbic acid and total phenolic contents, which was consistent with previous studies [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…We could speculate that the high total proanthocyanidin content made a major contribution to the antioxidant capacity, and our correlation analysis results also support this viewpoint. In our previous study, leaves from purple and green flowering stalks exhibited higher pigment, ascorbic acid, proanthocyanidin, flavonoid, and total phenolic contents compared to other edible parts [ 32 ]. Similarly, in this study, the total chlorophyll, total carotenoid, and total flavonoid contents were the highest in the leaves of the eight cultivars, with the exception of the total flavonoids in M3.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have confirmed remarkable differences in phytochemicals and antioxidant capacity among different organs and tissues of vegetables [ 20 , 21 , 22 ]. In our previous study, we found that the leaves of both purple flowering stalks and green flowering stalks had the higher content of health-promoting compounds, such as phenolics, compared to other edible parts [ 23 ]. The leaves of different variants of Amaranthus showed the highest content of total phenolics and FRAP values, while seeds and stalks had the lowest [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the health-promoting compounds in the leaves, there were also differences among the three tested vegetables. Previous studies have shown that chlorophyll, carotenoids, ascorbic acid, flavonoids and other health-promoting compounds have strong antioxidant capacity in vegetable crops [ 23 , 34 , 35 , 36 , 37 , 38 ], and phenolic compounds are also important antioxidants [ 39 , 40 , 41 ]. Our results suggested that for the content of chlorophyll and carotenoids, the trend was sweet potato > amaranth > malabar spinach.…”
Section: Discussionmentioning
confidence: 99%
“…In the southern region of China, purple flowering stalks (Brassica campestris var. purpuraria) are a popular vegetable during the winter and spring months [1]. They are herbaceous plants that grow in one or two years and belong to the Brassica family of Cruciferae [2].…”
Section: Introductionmentioning
confidence: 99%